Edibility and Medicinal Studies of Crinum ornatum in Comparison with Allium sativum - Lawal, Abubakar; Tan, Guan Huat; Alsharif, Ali Mohammed Ali (Pakistan Journal of Nutrition, 2015)
Historically, Allium sativum have been documented and valued for their spicy and medicinal qualities by many cultures around the globe for many years. Notwithstanding, medicinal activity of other bulb species such as Crinum ornatum have also been published. However, the bulb species of Crinum ornatum and Allium sativum were individually analyzed quantitatively for proximate compositions and flavonoids contents of the samples. Phytochemical and toxicological tests were carried out on the aqueous extracts of both species. These analyses were conducted in order to see spicy potentials of Crinum ornatum compared with Allium sativum. Proximate analysis results were presented as mean±standard deviation of three replicates, respectively; Crinum ornatum and Allium sativum contains 77.83±2.75 and 52.60±0.30% moisture, 4.67±0.58 and 4.50±0.27% ash, 0.67±0.29 and 2.98±0.03% crude lipid, 4.04±0.07 and 8.40±0.18% crude protein, 2.67±0.29 and 1.47±0.02% crude fibre, 87.96±0.46 and 82.65±0.04% available carbohydrate and 373.99 and 391.02 kcal/100 g energy value. Phytochemical screening for the two bulbs respectively revealed the presence of alkaloids, saponins, tannins, flavonoids, glycosides, cardiac-glycosides, volatile oils and steroids. The quantity of flavonoids in dried Crinum ornatum and Allium sativum are 52.4±0.02 and 29.20±0.29%, respectively. The LD50 result of both samples were, respectively higher than 3000 mg/kg for the tested animals. These results justifiably shows that, Crinum ornatum bulbs could be considered as potential spice which would serve in medicinal and culinary purposes.